Alteration of microbiota antibody‐mediated immune selection contributes to dysbiosis in inflammatory bowel diseases. Issue 8 (4th July 2022) - Michaud, Eva; Waeckel, Louis; Gayet, Rémi; Goguyer‐Deschaumes, Roman; Chanut, Blandine; Jospin, Fabienne; Bathany, Katell; Monnoye, Magali; Genet, Coraline; Prier, Amelie; Tokarski, Caroline; Gérard, Philippe; et al.
Abstract: Human secretory immunoglobulins (SIg) A1 and SIgA2 guide mucosal responses toward tolerance or inflammation, notably through reverse‐transcytosis, the apical‐to‐basal transport of IgA2 immune complexes via M cells of gut Peyer's patches. As such, the maintenance of a diverse gut microbiota requires broad affinity IgA and glycan–glycan interaction. Here, we asked whether IgA1 and IgA2‐microbiota interactions might be involved in dysbiosis induction during inflammatory bowel diseases. Using stool HPLC‐purified IgA, we show that reverse‐transcytosis is abrogated in ulcerative colitis (UC) while it is extended to IgA1 in Crohn's disease (CD). 16S RNA sequencing of IgA‐bound microbiota in CD and UC showed distinct IgA1‐ and IgA2‐associated microbiota; the IgA1 + fraction of CD microbiota was notably enriched in beneficial commensals. These features were associated with increased IgA anti‐glycan reactivity in CD and an opposite loss of reactivity in UC. Our results highlight previously unknown pathogenic properties of IgA in IBD that could support dysbiosis. Synopsis: IBD (both CD and UC) is characterized by dysbiosis and altered immune pathways that lead to and sustain prolonged inflammation in the gut. As IgA are the main drivers of commensal selection in the healthy gut, this study aimed at assessing subclass‐related structure and functions of IgA in both CD and UC. Evidence of a chain of subclass‐dependent functional disparities between CD and UC IgAs affecting antibody glycosylation, transport across epithelia, and affinity, which may interfere in optimal commensal selection to promote dysbiosis While only IgA2 could undergo RT in non‐IBD, IgA1 in CD had the ability to do so and neither IgA1 nor IgA2 were able to in UC. Despite predominant dual IgA1 and IgA2 binding on stool microbiota, CD associates with enriched commensal binding in the IgA1 + fraction, and UC with a marked reduction in IgA overall reactivity Abstract : IBD (both CD and UC) is characterized by dysbiosis and altered immune pathways that lead to and sustain prolonged inflammation in the gut. As IgA are the main drivers of commensal selection in the healthy gut, this study aimed at assessing subclass‐related structure and functions of IgA in both CD and UC.